A Filosofia Andina 1: Uma interpelaçãoao pensamento ocidental. Colonialismo, colonialidade e descolonização para uma interdiversidade de saberes (J. Estermann) - Manuel Tavares (EccoS – Revista Científica)
This paper is a reflection about the thinking of Josef Estermann, one of the most scholars academic of the andean thought and which present some of the principles of Andean philosophy which constitute a real questioning of the dominant Western thought for centuries. All the thought is characterized by its incompleteness. The Western thought has established itself as hegemonic and made invisible the cultural and epistemological alterities. The intercultural dialogue will help to dissolve the hegemonic pretension of the dominant thought and to give visibility to a more holistic and human way of thought.